The Changing Mix of Disequilibria During Transition : A Romanian Background - Daianu, Daniel (IMF Working Papers; Working Paper ;, 1994)
This paper looks at the dynamics of (dis)equilibria during post-command transition. It tries to define an optimal mix between external and internal disequilibrium and to apply this concept to the analysis of the Romanian economy. The forced adjustment of the balance of payments in the 1980s is presented as a prologue to the scrutiny of transformation policy underway; results and dilemmas of macro-stabilization are dealt with in this respect. The paper ends by providing some insights into the problematique of understanding (dis)equilibria in transforming economies.